Evaluasi Rehabilitasi Hutan dan Lahan (RHL) di Daerah Aliran Sungai (DAS) Juwana pada Kawasan Gunung Muria Kabupaten Pati - Surtiani, Yohan; Budiati, Lilin (Magister Pembangunan Wilayah dan Kota,Undip, 2015)
This research aims to develop a model program evaluation FLR at Juwana watershed area, especially the village of Mount Muria Klakahkasihan, Plukaran, Bageng, Sitiluhur Kingpin District of Pati regency and to review the positionÂ as a government agency responsible for RHL program. This study shows the percent achievement FRL programs in the watershed Juwana area of Mount Muria Pati regency of 65.8%. The achievement consists of (1) a prerequisite Sustainable RHL Program Implementation (10%), (2) management and protection of ecological resources (29%), (3) sustainable forest production systems (4%), (4) Increased participation and Socio-economic communities (34%), (5) RHL Policy Implementation (23%). The position of the Department of Forestry and Plantation institutions Pati regency in the position grow and build . Fore suggested Forestry and Plantation Pati regency make improvements FRL implementation strategy: (1) institutional strengthening, (2) development of networking and integration of programs and policies across sectors and organizations for the development of public services.